PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI MI MUHAMMADIYAH CECE - Nur Irdayanti; Ismail; Wulandari (STKIP Subang, 2026)
This study aims to enhance students’ learning outcomes through the use of the Jigsaw cooperative learning model in Pancasila Education. The issue addressed in this study is the low level of learning outcomes resulting from teacher-centered learning. This research employed Classroom Action Research (CAR) consisting of two cycles, namely planning, implementation, observation, and reflection stages. The participants were fourth-grade students of MI Muhammadiyah Cece. Data were gathered through observation and tests, and then analyzed using descriptive quantitative techniques. The results revealed a significant improvement in students' learning outcomes. In the pre-cycle stage, classical completeness was 41.18%. In cycle I, the average score rose to 74.12 with 52.94% completeness. In cycle II, the average score increased to 93.24 with 88.24% completeness. These findings demonstrate that the Jigsaw cooperative learning model effectively enhances students’ learning outcomes, participation, and collaboration skills. Therefore, this model can be applied as an alternative learning strategy in elementary education.